Keratoplasty for keratoconus: advantages and disadvantages - M. M. Bikbov; E. L. Usubov; A. F. Zaynetdinov (Российский офтальмологический журнал)
Keratoconus is a progressive bilateral corneal ectasia, accompanied by loss of vision due to high irregular astigmatism, which is the leading indication for corneal transplantation. The review presents a variety of surgical corneal transplantation techniques for keratoconus available today and discussed their advantages and disadvantages.